Hubungan Celebrity Worship dengan Problematic Social Media Use pada Penggemar BTS di Kota Bandung - Dinda Juwita Ratu Hapsari; Indri Utami Sumaryanti (Bandung Conference Series: Psychology Science, 2022)
Abstract. Korean Wave is one of impact from social media. KPop fans Mostly use social media to find information about their idols. This situation shows how social media has become important for fans to support their fanatical behavior. Social media is also a bridge between fans and their idols. The interactions lead to parasocial relationships that develop into celebrity worship. Fans who feel they have an attachment to their idols will try to continue to access social media to get the latest information on their idols. Celebrity worship usually appears in adolescents and decreases with age, but the existing phenomenon shows that there are still individuals in early adulthood, who still perform celebrity worship behavior. The purpose of this study was to obtain empirical data the relationship between celebrity worship and problematic social media use on BTS fans in Bandung. In this study, the research method is correlational and the sampling technique used is purposive sampling with the number of respondents as many as 119 people. The measuring instruments used is Celebrity Attitude Scale (CAS) and Bergen Social Media Addiction Scale (BSMAS). The analytical technique used is the rank spearman correlation test and obtained a correlation coefficient value of 0.127 and a significance value of 0.167, meaning p > 0.05, which means that there is no relationship between celebrity worship and problematic social media use. Abstrak. Korean Wave merupakan salah satu dampak dari media sosial. Penggemar K-Pop menggunakan media sosial untuk mencari informasi tentang idola mereka. Situasi ini menunjukkan media sosial penting bagi penggemar untuk mendukung perilaku fanatik mereka. Media sosial menjadi jembatan antara penggemar dan idolanya. Interaksi tersebut mengarah pada hubungan parasosial yang berkembang menjadi celebrity worship. Fans yang merasa memiliki keterikatan dengan idolanya akan berusaha terus mengakses media sosial untuk mendapatkan informasi terbaru idolanya. Celebrity worship biasanya muncul pada masa remaja dan menurun seiring bertambahnya usia, namun fenomena yang ada menunjukkan masih ada individu pada masa dewasa awal yang masih melakukan celebrity worship. Tujuan dari penelitian ini adalah untuk mendapatkan data empiris hubungan antara celebrity worship dan problematic social media use pada penggemar BTS di Bandung. Dalam penelitian ini metode penelitian yang digunakan adalah korelasional dan teknik pengambilan sampel yang digunakan adalah purposive sampling dengan jumlah responden sebanyak 119 orang. Alat ukur yang digunakan yaitu Celebrity Attitude Scale (CAS) dan Bergen Social Media Addiction Scale (BSMAS). Teknik analisis yang digunakan adalah uji korelasi rank spearman dan diperoleh nilai koefisien korelasi sebesar 0,127 dan nilai signifikansi sebesar 0,167 yang berarti p > 0,05, artinya tidak ada hubungan antara celebrity worship dengan problematic social media use.